Genetic predisposition to digital device use and the risk of five psychiatric disorders - Liu, Qi; Zhang, Zhen (Frontiers in Psychiatry, 2025)
BackgroundPsychiatric disorders were observationally related to digital device use, but causality and direction remained unclear. We aimed to uncover the causal links between digital device use and five psychiatric disorders risk utilizing the two-sample Mendelian Randomization method.MethodsWe obtained genetic variants related to digital device use from the UK Biobank’s genome-wide association study and psychiatric disorders data from the Psychiatric Genomics Consortium. The primary analysis employed the inverse-variance weighted method, complemented by sensitivity analyses to determine heterogeneity and pleiotropy.ResultsThere were causal relationships between genetically increased mobile phone use [odds ratio (OR) = 1.75, 95% confidence interval (CI): 1.31-2.33], more television watching (OR = 3.39, 95% CI: 2.64-4.35) and a higher risk of attention-deficit/hyperactivity disorder (ADHD). Genetically determined duration of computer use was also causally related to the risk of autism spectrum disorder (ASD) (OR = 2.66, 95%CI: 1.82-3.88). Conversely, ADHD was significantly positively associated with playing computer games (β = 0.021, 95%CI: 0.010-0.032) and watching television (β = 0.030, 95%CI: 0.010-0.049). Also, a significant inverse associations of major depression disorder (MDD) with playing computer games was observed (β = 0.008, 95%CI: 0.003-0.013).ConclusionsOur findings indicate potential causal links between genetic disposition to use digital devices and psychiatric disorders, such as ADHD, ASD, and MDD, highlighting the importance of digital device use in both prevention and management of these disorders.